A comparative analysis of passive constructions in English, Afrikaans and isiXhosa: Grammar and acquisition - Potgieter, Anneke Perold (Stellenbosch papers in linguistics, 2017)
Whilst literature on the acquisition of passive constructions by speakers of European languages abounds, there is a dearth of grammatical descriptions of passive constructions in (especially South) African languages that may serve as a basis for acquisition studies. Furthermore, the majority of studies have focused on monolingual participants only, leaving the typical multilingual African language acquisition context underrepresented. This paper addresses these gaps in the literature by offering an in-depth cross-linguistic comparison of passive constructions in the three official languages of the Western Cape, a province in South Africa, namely the Germanic languages English and Afrikaans and the Southern Bantu language isiXhosa. The grammatical description of passives in these languages covers the nature of the passive verb complex; the placement of the object and, in long passives, subject arguments; movement of the object argument across clause boundaries in infinitival clauses; existential passive constructions; case assignment; restrictions on passivisation; and verbal versus adjectival passive constructions. This information may serve as basis for finer syntactic analyses, studies of cross-linguistic bootstrapping, and also descriptive grammars. The paper finally presents normative data for the acquisition of passive constructions by monolingual speakers of English and by speakers of languages closely related to Afrikaans and isiXhosa (such data not yet being readily available for the latter two languages). The reported higher frequency of passive constructions in Bantu languages is cited as a possible explanation for the relatively early acquisition of this otherwise notoriously late-acquired construction.